Oligotyping reveals stronger relationship of organic soil bacterial community structure with N-amendments and soil chemistry in comparison to that of mineral soil at Harvard Forest, MA, USA - Turlapati, Swathi A.; Minocha, Rakesh; Long, Stephanie; Ramsdell, Jordan; Minocha, Subhash C. (Frontiers in Microbiology, 2015)
The impact of chronic nitrogen amendments on bacterial communities was evaluated at Harvard Forest, Petersham MA. Thirty soil samples (3 treatments x 2 soil horizons x 5 subplots) were collected in 2009 from untreated (control), low nitrogen-amended (LN; 50 kg NH4NO3 ha-1 yr-1) and high nitrogen-amended (HN; 150 kg NH4NO3 ha-1 yr-1) plots. PCR-amplified partial 16S rDNA sequences made from soil DNA were subjected to pyrosequencing (Turlapati et al., 2013) and analyses using oligotyping. The parameters M (the minimum count of the most abundant unique sequence in an oligotype) and s (minimum number of samples in which an oligotype is expected to be present) had to be optimized for forest soils because of high diversity and the presence of rare organisms. Comparative analyses of the pyrosequencing data by oligotyping and OTU (Operational Taxonomic Unit) clustering tools indicated that the former yields more refined units of taxonomy with sequence similarity of ≥99.5%. Sequences affiliated with 4 new phyla and 73 genera were identified in the present study as compared to 27 genera reported earlier from the same data (Turlapati et al., 2013). Significant rearrangements in the bacterial community structure were observed with N-amendments revealing the presence of additional genera in N-amended plots with the absence of some that were present in the control plots. Permutational MANOVA analyses indicated significant variation associated with soil horizon and N treatment for a majority of the phyla. In most cases soil horizon partitioned more variation relative to treatment and treatment effects were more evident for the organic horizon. Mantel test results for organic soil showed significant positive correlations between bacterial communities and most soil parameters including NH4 and NO3. In mineral soil, correlations were seen only with pH, NH4 and NO3. Regardless of the pipeline used, a major hindrance for such a study remains to be the lack of reference databases for fo